Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
x- intercept is at [tex]( - 3 \frac{2}{3} ,0)[/tex].
y- intercept is at [tex](0,1 \frac{5}{6} )[/tex].
Step-by-step explanation:
The x-intercept occurs when y=0.
Thus, substitute y= 0 into the equation to find the x- intercept.
-3x +6y= 11
When y= 0,
-3x +6(0)= 11
-3x= 11
x= 11 ÷ (-3)
[tex]x = - \frac{11}{3} \\ x = - 3 \frac{2}{3} [/tex]
The y-intercept occurs at x= 0.
When x= 0,
-3(0) +6y= 11
6y= 11
y= 11÷ 6
[tex]y = 1\frac{5}{6} [/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.